2019
DOI: 10.1111/apt.15403
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review with meta‐analysis: risk factors for thiopurine‐induced leukopenia in IBD

Abstract: Background: Thiopurine-induced leukopenia, a frequently observed and potentially life-threatening adverse event, complicates the clinical management of IBD patients. Aim:To assess risk factors for thiopurine-induced leukopenia in IBD.Methods: MEDLINE, EMBASE, BIOSIS and Cochrane library were searched for studies reporting at least one risk factor for thiopurine-induced leukopenia.Pooled odds ratio (OR) was calculated for each potential risk factor using a random effects model. Studies that were not eligible fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 103 publications
(318 reference statements)
2
22
1
Order By: Relevance
“…31 A recent systematic review and meta-analysis on predictive factors of thiopurine induced leucopenia in more than 11 000 IBD patients showed that patients with NUDT15 R139C variant have 6.9-fold higher odds of developing leucopenia (3.9-fold for TPMT variants). 32 Our study further reiterates this strong association. was identified in two third of patients (12.3% homozygous and 54.3% heterozygous mutation variant).…”
Section: Discussionsupporting
confidence: 78%
“…31 A recent systematic review and meta-analysis on predictive factors of thiopurine induced leucopenia in more than 11 000 IBD patients showed that patients with NUDT15 R139C variant have 6.9-fold higher odds of developing leucopenia (3.9-fold for TPMT variants). 32 Our study further reiterates this strong association. was identified in two third of patients (12.3% homozygous and 54.3% heterozygous mutation variant).…”
Section: Discussionsupporting
confidence: 78%
“…The potential use of a steady-state 6TGN level above 450 pmol/8 × 10 8 red blood cells (RBC) to predict toxicity is still controversial[9-14]. Several studies have reported that 6TGN levels are not significantly correlated with TIL, and no applicable therapeutic range for 6TGN has been determined[15-18]. For example, a prospective study found that only three out of ten Japanese patients with TIL exhibited high 6TGN levels (> 450 pmol/8 × 10 8 RBC)[17].…”
Section: Introductionmentioning
confidence: 99%
“…These findings highlight the importance of NUDT15 genotyping, alongside TPMT phenotype, or genotype testing. This is supported by a recent systematic review and meta-analysis (23), and recently published guidelines provide suggested dosing regimens in patients with TPMT or NUDT15 variants (24).…”
Section: Predictors Of Toxicitymentioning
confidence: 81%
“…A recent multicenter, international retrospective study showed that 6-TGN levels were associated with mucosal healing, and that a level of 397 pmol/10 8 RBC was 86.7% specific but only 35.3% sensitive for mucosal healing (75). However, higher 6-TGN levels are also associated with increased rates of early or late myelotoxicity (23), particularly above 450 pmol/8 × 10 8 RBC (76), and so a fine balance exists between response and toxicity. Interestingly, while a lower thiopurine dose may be sufficient for Asian patients, as discussed above, it is the 6-TGN and not the dose that was associated with mucosal healing in a cohort including a large proportion of Chinese patients (75).…”
Section: Predictors Of Response To Thiopurinesmentioning
confidence: 99%